Humanisme dalam Pembelajaran Matematika di Era Digital: Telaah filosofis atas Ancaman Dehumanisasi - Siti Habiba; Alifiani (Mandalika Mathematics and Educations Journal, 2026)
Mathematics education in the digital era faces significant challenges, including the risk of dehumanization when students become overly dependent on technology, potentially hindering essential mathematical thinking, reasoning, and reflection. This article aims to philosophically examine mathematics education in the digital era from a humanistic perspective, particularly regarding the threat of dehumanization and efforts to preserve the human dimension in learning. A Systematic Literature Review (SLR) guided by PRISMA was conducted on national and international accredited journal articles from Scopus, ERIC, ResearchGate, SINTA, and Google Scholar published between 2017 and 2025, resulting in 10 relevant articles for thematic analysis. The findings indicate that humanistic philosophy positions students as whole individuals, emphasizes the teacher’s role as a dialogical companion and value guide, and views digital technology as a supportive tool rather than a replacement for human interaction. The study concludes that integrating humanistic values in digital mathematics education is essential to prevent dehumanization, strengthen character development, and ensure learning remains meaningful, ethical, and human centered.